The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.1051/e3sconf/202128602008
|View full text |Cite
|
Sign up to set email alerts
|

The comparison of thermal comfort test results in selected traditional and modern buildings

Abstract: The use of renewable energy sources in buildings is more and more common (both for heating and cooling purposes, as well as electricity generation). The paper focuses on the thermal comfort tests in two buildings: the traditional one (that uses non-renewable sources of energy) and the modern intelligent building “Energis” of Kielce University of Technology. The thermal sensations of students in these two buildings have been compared based on the questionnaire survey and conclusions have been drawn regarding th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 13 publications
(10 reference statements)
3
10
0
Order By: Relevance
“…Only one room was too cold for the respondents, therefore they want the temperature in the room to be warmer. Comparing with the results from [3], the respondents preferred warmer thermal conditions. The respondents were also asked about the assessment of air humidity (Fig.…”
Section: Resultsmentioning
confidence: 77%
See 1 more Smart Citation
“…Only one room was too cold for the respondents, therefore they want the temperature in the room to be warmer. Comparing with the results from [3], the respondents preferred warmer thermal conditions. The respondents were also asked about the assessment of air humidity (Fig.…”
Section: Resultsmentioning
confidence: 77%
“…International standards ([1], [2]) on thermal comfort determination were developed after the foundations laid by a pioneer in this field, namely O. Fanger originating from the 1960's. Recent studies [3] on thermal comfort in a smart building have shown that there is a difference between subjective feelings and actual results. Similar conclusions were observed in the authors [4,5].…”
Section: Introductionmentioning
confidence: 98%
“…However, for the second building, research was carried out in January 2022. Air temperature, relative air humidity and air velocity for the traditional building are 27.7 o C, 47.60% and 0.05 m/s [3], while for the intelligent one: 25.1 o C, 29.72% and 0.09 m/s.…”
Section: Methodsmentioning
confidence: 95%
“…In this study, a study was carried out for two buildings, a school building and an intelligent building of Energis of the Kielce University of Technology. The results for the first building were taken from the article [3]. However, for the second building, research was carried out in January 2022.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation